The autism spectrum and further education : a guide to good practice - Breakey, Christine, 1952- (J. Kingsley, 2006)
This guide for professionals working with students with autism spectrum conditions (ASCs) in further education meets the increasing demand for information and support on this subject. Christine Breakey provides useful guidelines and practical advice on teaching young adults successfully and confidently, emphasising the development of resources and practical skills for use specifically in FE colleges. The author covers all the key areas and offers strategies and solutions for communicating effect.